2020
DOI: 10.1371/journal.pone.0235332
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D level and bronchopulmonary dysplasia: A systematic review and meta-analysis

Abstract: Neonatal vitamin D deficiency is common and is associated with development of pulmonary disease in children and adults. While the role of vitamin D in normal lung development is well established, the association between vitamin D deficiency and bronchopulmonary dysplasia (BPD) remains unclear. The present meta-analysis was conducted to evaluate the relationship between vitamin D and BPD. We identified relevant studies (n = 8) using the PubMed, EMBASE, Cochrane Library, and KoreaMed databases and applied the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…In the present study, we showed that early vitamin D supplementation is significantly associated with the occurrence of BPD but not classification in preterm newborns. These results are in line with a comprehensive meta-analysis conducted by Park et al 7 They included 251 infants out of 909 infants were diagnosed with BPD.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we showed that early vitamin D supplementation is significantly associated with the occurrence of BPD but not classification in preterm newborns. These results are in line with a comprehensive meta-analysis conducted by Park et al 7 They included 251 infants out of 909 infants were diagnosed with BPD.…”
Section: Discussionsupporting
confidence: 89%
“…Vitamin D is a promising candidate due to its anti-inflammatory and lung-growth-promoting properties. Its therapeutic potential is derived from the current meta-analysis that shows that low vitamin D levels at birth predispose the infants to BPD [ 88 ]. The experimental evidence suggests a significant benefit that can, at least partly, be attributed to the inhibition of key features of the inflammatory response [ 89 , 90 ].…”
Section: Clinical Approaches To Prevent Ros-induced Lung Injury and Bpdmentioning
confidence: 99%
“…These epigenetics diets include polyphenols (epigallocatechin-3-gallate, resveratrol, genistein), vitamins (vitamins c and d, folate, choline), isothiocyanates, withaferin a, and selenium. Perinatal vitamin D deficiency and low vitamin D levels have played a crucial role in neonatal BPD [156,157]. Significantly, vitamin D can directly stimulate fetal pulmonary artery endothelial cell and alveolar epithelial type II cell growth and function to prevent BPD development in preterm infants [158].…”
Section: Perspectives For Treatment and Prevention Of Neonatal Chronic Lung Diseasementioning
confidence: 99%